Pengaruh Media Animasi Interaktif Terhadap Motivasi Belajar Pada Mata Pelajaran Fisika SMA Negeri 2 Surabaya - Hakimi, Ahmad Taufiqul; Anam, Karafi Nur (Journal of Science and Mathematics Education, 2025)
This study aims to determine the effect of interactive animation media on students’ learning motivation in Physics subjects at SMA Negeri 2 Surabaya. The background of this research is based on the low interest and motivation of students in learning Physics, which is often considered difficult and boring. The use of conventional learning media, which tends to be less interactive, often fails to attract students' attention and interest. Therefore, interactive animation media is expected to be an effective alternative solution to improve learning motivation. The research method used is a quasi-experimental design with a pretest-posttest control group. The research sample consisted of two classes: the experimental class, which used interactive animation media, and the control class, which used conventional lecture methods. The instrument used was a validated and reliability-tested learning motivation questionnaire. The results of the study show that there is a significant difference in learning motivation between students in the experimental class and those in the control class. Students who learned using interactive animation media showed a higher increase in learning motivation compared to those who learned through conventional methods. These findings indicate that the use of interactive animation media can positively contribute to improving students' motivation in learning Physics. Therefore, teachers are encouraged to integrate interactive animation media as part of their classroom teaching strategies.